TECHNICAL AND ECONOMIC JUSTIFICATION OF THE APPLICATION OF COAL GASIFICATION INSTALLATION AT ANGREN TPP - Kavkatbekov, Murodjon; Babakhodjaev, Rakhimjan (Innovatsion texnologiyalar, 2024)
The main goal of introducing gasification plants is to reduce harmful atmospheric emissions from direct combustion of coal, as well as to increase the service life of process equipment. The relevance of the work lies in the feasibility study of the implementation of a layered gasification installation for Angren brown coal, as well as the possibility of using the resulting generator gas as fuel for illumination in boilers of the TP-230-2 type at the Angren Thermal Power Plant. The article theoretically calculates the capital and operating costs of the proposed installation. The capital and operating costs of the proposed installation are theoretically calculated. Angren brown coal of the BOMSSH B-2 grade was used as a raw material. The values of producer gas were experimentally obtained, the results of which were compared with the values of underground gas of Yerostigaz JSC. Based on the calculation of the technical and economic indicators of a layered gas generator for a boiler of the ТП-230-2 type at the Angren TPP, data on total investment costs, annual benefits, savings in annual operating costs for the repair of boiler equipment, payback period, and reduction of emissions into the atmosphere were obtained. The quality indicators of the generator gas allow it to be used as an alternative fuel for gas from the (UCG) plant of Yerostigaz JSC. The payback period of the project is 3 years, which classifies it as an average payback period. Based on certain performance indicators, we can say that the investment project is economically feasible and financially sound.